Waiting to Inhale: On Sniffing in Conversation. Issue 1 (2nd January 2020) - Hoey, Elliott M.
ABSTRACT: This article examines sniffing in everyday conversations. It builds on prior conversation analytic research on respiratory conduct, which has shown how things like inbreaths, sighs, and laughter are delicately organized and consequential components of the social occasions into which they figure. Sniffing—the swift, audible, intake of breath through the nasal passage—is analyzed by reference to its sequential placement in talk. Using a collection of 70 cases of sniffs in naturally occurring conversations, two recurrent uses of sniffing are described. Sniffs placed before or during a turn-at-talk serve to delay turn progression. And sniffs placed in the postcompletion space of a turn can indicate its completion. This association between postcompletion sniffing and turn completion is further supported through a comparison with postcompletion inbreaths. By situating sniffing in its sequential contexts, the organization of breathing is shown to be bound up with the organization of speaking. Data are in American and British English.